Formalized peer referral to HIV pre-exposure prophylaxis supported with self-testing: a mixed-methods pilot study among young Kenyan women - McGowan, Maureen; Wairimu, Njeri; Reedy, Adriana M.; Mogere, Peter; Culquichicon, Carlos; Njeru, Irene; Malen, Rachel C.; Jahn, Albrecht; Bärnighausen, Till; Roche, Stephanie D.; Ngure, Kenneth; Ortblad, Katrina F. (Frontiers in Public Health, 2024)
Background The uptake of daily oral HIV pre-exposure prophylaxis (PrEP)—a highly effective intervention—remains low among African adolescent girls and young women (AGYW) who could benefit. AGYW who initiate PrEP often do so through informal peer referral, which may be enhanced with formalized peer referral and peer-delivered HIV self-testing (HIVST). To understand the feasibility of this PrEP referral model among AGYW, we conducted a pilot study in Kenya. Method From March to May 2022, we recruited AGYW (≥16–24 years) using PrEP (i.e., “peer providers”) from public healthcare clinics in Kiambu County and trained them on HIV prevention, HIVST use, and peer-supported linkage to clinic-based HIV services. Following training, peer providers received eight HIVST kits and were encouraged to refer four peers (i.e., “peer clients”) to PrEP. We completed surveys with peer providers and clients one month following intervention delivery to assess PrEP initiation among peer clients. Later, we conducted focus group discussions (FGDs) with peer providers and clients to identify factors that facilitated or challenged intervention outcomes. Results We trained 16 peer providers (median age: 23 years, IQR 21–24) who reported delivering the intervention to 56 peer clients; 30 peer clients (median age: 21 years, IQR 19–22) contacted the study team and were enrolled. Most of the enrolled peer clients reported behaviors associated with HIV risk (e.g., condomless sex; 80%, 24/30) and were PrEP-naïve (87%, 26/30). At one-month, PrEP initiation among eligible PrEP-naïve peer clients was high, as reported by providers (78%, 43/55) and clients (85%, 22/26); recent HIVST use was also high among peer clients (provider report: 95%, 53/56; client report: 97%, 29/30). In the FGDs, participants reported that intervention outcomes were facilitated by close preexisting relationships, HIVST assistance, and being escorted to clinic-based HIV services by peer providers; intervention barriers included conflicting priorities and limited HIVST experience. Conclusion A formalized model of peer referral with HIVST delivery supported PrEP initiation among Kenyan AGYW. These findings demonstrate the potential for peer-delivered interventions to engage AGYW in HIV prevention services; however, more research is needed on the effectiveness and sustainability of this approach at scale.